2020
DOI: 10.1155/2020/3921796
|View full text |Cite
|
Sign up to set email alerts
|

Sinapic Acid Ameliorates Oxidative Stress, Inflammation, and Apoptosis in Acute Doxorubicin-Induced Cardiotoxicity via the NF-κB-Mediated Pathway

Abstract: In the present study, we explored SA’s activity against DOX-induced cardiotoxicity and revealed its underlying mechanisms. Male Wistar rats (weight, 190-210g; n=6) were randomly divided into four groups: group I, normal control; group II, DOX 15 mg/kg via intraperitoneal (ip) route; group III, administered DOX+SA 20 mg/kg; and group IV, administered DOX+captopril (CAP 30 mg/kg). SA and CAP were administered orally for seven days, and DOX (15 mg/kg) was injected intraperitoneally an hour before SA treatment on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 50 publications
10
39
0
Order By: Relevance
“…SA has potent anti-lipid peroxidation and free radical scavenging activities ( Chen, 2016 ). These results are consistent with those of previous reports ( Chen, 2016 ; Raish et al, 2018a ; Raish et al, 2018b ; Raish et al, 2019 ; Bin Jardan et al, 2020 ), in that gastric mucosal apoptotic injuries have been shown to by prompted by oxidative stress and inflammatory cytokines via the intrinsic mitochondrial pathway. The oxidative-stress-induced apoptosis controlled by the antiapoptotic Bcl2 and pro-apoptotic Bax and caspase-3 proteins plays a significant role in the disruption of gastric mucosal wall integrity after ethanol intubation ( Durkin et al, 2006 ; Liu et al, 2018 ; He et al, 2019 ).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…SA has potent anti-lipid peroxidation and free radical scavenging activities ( Chen, 2016 ). These results are consistent with those of previous reports ( Chen, 2016 ; Raish et al, 2018a ; Raish et al, 2018b ; Raish et al, 2019 ; Bin Jardan et al, 2020 ), in that gastric mucosal apoptotic injuries have been shown to by prompted by oxidative stress and inflammatory cytokines via the intrinsic mitochondrial pathway. The oxidative-stress-induced apoptosis controlled by the antiapoptotic Bcl2 and pro-apoptotic Bax and caspase-3 proteins plays a significant role in the disruption of gastric mucosal wall integrity after ethanol intubation ( Durkin et al, 2006 ; Liu et al, 2018 ; He et al, 2019 ).…”
Section: Discussionsupporting
confidence: 94%
“…We found that the dose response in terms of GUI and PGE2 levels for the three dose levels of SA, 40 mg/kg had the maximum gastroprotective effect. This was further corroborated by our previous research, which indicated that 40 mg/kg of SA has maximum antioxidant, anti-inflammatory, and antiapoptotic activity ( Raish et al, 2018a ; Raish et al, 2019 ; Bin Jardan et al, 2020 ). Several reports have implicated alcohol in gastric mucosal damage and upper gastrointestinal bleeding ( Teyssen and Singer, 2003 ; Simoes et al, 2019 ).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations